2017
DOI: 10.1016/j.eatbeh.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and temporal frame: Reducing frequency of snacking by highlighting immediate health benefits

Abstract: The current study aimed to examine the effect of giving temporally framed health information regarding either the immediate or long-term health consequences of consuming high-calorie snacks, for people with high Negative Urgency (a dimension of impulsivity), and for those primed with impulsivity. We expected that for participants with high Negative Urgency, and those primed with impulsivity, information which detailed the immediate health benefits of avoiding snack consumption would be more effective than info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Stronger identification with the female identity also was shown to correlate with DE, although not independently from perceived perfection pressure from women (fSPP) and urgency. These findings extend on previous studies showing that strength of identification (in‐group affect) with the female identity may relate to DE (Hesse‐Biber et al ., ), and adds to the clinical literature on the relationship between impulsivity, perfectionism, and DE (Pavey & Churchill, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Stronger identification with the female identity also was shown to correlate with DE, although not independently from perceived perfection pressure from women (fSPP) and urgency. These findings extend on previous studies showing that strength of identification (in‐group affect) with the female identity may relate to DE (Hesse‐Biber et al ., ), and adds to the clinical literature on the relationship between impulsivity, perfectionism, and DE (Pavey & Churchill, ).…”
Section: Discussionsupporting
confidence: 90%
“…While early studies suggested that self-control (and its facets) was a personality trait, more large scale investigations have suggested that self-control is far more context sensitive than initially believed (Hagger, Chatzisarantis, Alberts et al, 2016;Lurquin, Michaelson, Barker et al, 2016). Impulsive eating especially appears to be a specific response to context (Haynes, Kemps & Moffitt, 2016a, 2016bPavey & Churchill, 2017). For example, one study showed that when participants who scored lower on self-control scales believed that their peers had a norm of eating less, they were better able to resist the temptation of sugary pastries (Robinson et al, 2016).…”
Section: Self-control Negative Urgency and Dementioning
confidence: 99%
“…Affiliating oneself with the female identity also was shown to correlate with DE, although not independently from perfectionism and urgency. These findings extend on previous studies showing that strength of identification (in-group affect) with the female identity may relate to DE (Hesse-Biber et al, 2006), and adds to the clinical literature on the relationship between impulsivity, perfectionism, and DE (Pavey & Churchill, 2017). We also believe that understanding how perfectionism pressure relates to impulsivity may lead to better clinical outcomes for reducing DE.…”
Section: Discussionsupporting
confidence: 88%
“…While initial studies suggested that self-control (and its facets) was a personality trait, more large-scale investigations have suggested that self-control is far more context sensitive than initially believed (Hagger et al, 2016;Lurquin et al, 2016). Impulsive eating especially appears to be a specific response to context (Haynes, Kemps, & Moffitt, 2016a;Haynes et al, 2016b;Pavey & Churchill, 2017). For example, one study showed that when participants who scored lower on self-control scales believed that their peers had a norm of eating less, they were better able to resist the temptation of sugary pastries (Robinson et al, 2016).…”
Section: Self-control Negative Urgency and Dementioning
confidence: 99%
“…Overweight and obesity are a serious burden on both the individual and society, endangering health and increasing the risk of mortality, which has reached epidemic proportions in developed countries and affects around 46% of the world's population over the age of 19 (1). According to the results of the 2014 Hungarian Diet and Nutritional Status Survey, almost two-thirds of adults are overweight and 28.2% of men and 31.5% of women are obese (2).…”
Section: Introductionmentioning
confidence: 99%